Integrasi Syariah dengan Tasawuf - Asep Usman Ismail (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: Shariah Integration in Sufism. Islam is a religion that integrates Islamic principles and morals (sufism) on a basis of creed. For the prophet Rasulullah, this integration was reflected in his attitude which consistently obeyed the shariah in personal and social life (worship and mu‘âmalah). But on the other hand, he was a man who spent most nights with his head bowed, and shedding tears yearning for God. His heart is always connected with God. However, his loging for God gave birth to kindess to others forever with universal human value. The integration of both kindness and values can be apart, but it will continue to be championed by the Islamic scholars to draw closer together and re join in symphony. The Sunnah asserted only by intergrating both of them, joy of the world and the hereafter will materialise because they meet the needs of individual, social, and spiritual of human beings in an integrated manner.Keywords: âqîdah, shariah, fiqh, jurists, ihsân, sufism, the integrationAbstrak: Integrasi Syariah dengan Tasawuf. Islam  adalah agama yang memadukan syariah dan akhlak (tasawuf) di atas landasan akidah. Pada diri Rasulullah Saw. integrasi tersebut tercermin pada sikap beliau yang konsisten mematuhi syariah dalam kehidupan pribadi dan sosial (ibadah dan muamalah).  Sementara pada sisi lain, beliau adalah seorang yang melewati sebagian malamnya dengan rukuk dan sujud, serta tetes air mata kerinduan kepada Allah. Hati beliau senantiasa terpaut dengan Allah. Namun, kerinduan beliau kepada Allah melahirkan kebaikan kepada sesama tanpa mengenal musim dengan cita rasa kemanusiaan universal. Integrasi keduanya bisa merenggang, namun akan terus diperjuangkan oleh ulama hingga mendekat dan menyatu kembali secara simponi. Sunah Nabi menegaskan, hanya dengan memadukan keduanya, kebaikan dunia dan akhirat akan terwujud, karena keduanya memenuhi kebutuhan individu, sosial, dan spiritual manusia secara terpadu.Kata Kunci: akidah, syariah, fikih, fukaha, ihsân, tasawuf, integrasiDOI: 10.15408/ajis.v12i1.987